Motivators and barriers of adherence to hemodialysis among patients with end stage renal disease (ESRD) in Rwanda: A qualitative study - Marie Claire Mukakarangwa; Geldine Chironda; Aimable Nkurunziza; Flavien Ngendahayo; Busisiwe Bhengu (Elsevier, 2020)
Background: Worldwide, End stage renal disease (ESRD) is a public health concern increasing the number of patients maintained on the first choice of Renal Replacement Therapy (RRT) namely hemodialysis. Motivators and barriers to hemodialysis among ERSD patients in Rwanda are not well documented. Objective: The objective of the study was to explore the barriers and motivators of adherence to hemodialysis among end stage renal disease (ESRD) patients in Rwanda. Methods: The study used a qualitative approach. The purposive sampling strategy was used to select study participants. The data were collected using a semi-structured interview schedule which elicited barriers to and motivators of adherence to hemodialysis among ERSD patients. Qualitative data were analysed using a thematic framework approach. Results: The identified motivators of adherence to hemodialysis were family support, hope for renal transplant, alleviation of symptoms, to prolong life, improved quality of life and fear of death. Barriers included poverty, uncertain transport, treatment related complications and long distance. Conclusions: Patients with ESRD in Rwanda face numerous barriers to adherence to hemodialysis. Healthcare providers and other stakeholders need to be aware of the motivators and barriers to provide effective renal replacement therapies for better health outcomes.